Phylogenetic analysis of transparent gobies in three Sumatran lakes, inferred from mitochondrial Cytochrome Oxidase I (COI) gene - DEWI IMELDA ROESMA; DJONG HON TJONG; DYTA RABBANI AIDIL (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Roesma DI, Tjong DH, Aidil DR. 2020. Phylogenetic analysis of transparent gobies in three Sumatran lakes, inferred from mitochondrial Cytochrome Oxidase I (COI) gene. Biodiversitas 21: 43-48. The transparent gobies fish found in three lakes in Sumatra island is known as Rinuak fish (in Maninjau Lake and Singkarak Lake, West Sumatra, Indonesia) or Badar fish (in Siais Lake, North Sumatra, Indonesia), and are morphologically very similar to the Gobiopterus brachypterus. The phylogenetic study was carried out by analyzing 619 base pairs of the mitochondrial DNA cytochrome oxidase subunit I (COI) gene in 12 fish individuals from the three lakes. Rinuak and Badar fish in three populations have four haplotypes. The sequence divergences in and between populations are very low (0.0-0.5%). This value indicates that Rinuak and Badar fish are the same species with low genetic diversity. The phylogenetic tree illustrates that this fish belongs to the group of Gobiidae and a sister taxon from G. brachypterus.